Craniomaxillofacial Trauma in Dogs—Part II: Association Between Fracture Location, Morphology and Etiology - De Paolo, Mercedes H.; Arzi, Boaz; Pollard, Rachel E.; Kass, Philip H.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2020)
Treatment of craniomaxillofacial (CMF) trauma in dogs requires a thorough understanding of the CMF skeletal structures involved. The human medical literature has several examples of CMF trauma and fracture classification, including the classically described Le Fort fractures. The recent classification schemes require large studies using computed tomography (CT). In the veterinary medical literature, such studies are lacking. The aims of part II of this retrospective study were to use a large number of CT studies of dogs evaluated for CMF trauma to determine whether specific fracture locations in the CMF region occur concurrently, and whether trauma etiology influences fracture morphology. This information may then be used to form a fracture classification scheme in the future. The medical records and CT studies of 165 dogs over a 10-year period were evaluated. The skeletal location of CMF fractures as well as the severity of displacement and fragmentation of each fracture was recorded. Dogs’ demographic data and trauma etiology were also recorded. Fractured portions of the mandible tended to occur with fractures of adjacent bones, with the major exception of symphyseal separation, which occurred simultaneously with fractures of the cribriform plate. Fractures of the maxillary bone were accompanied by many concurrent fractures affecting the majority of the midface, skull base, and cranial vault. When the zygomatic bone was fractured, the other bones comprising the orbit also tended to fracture. Fractures of the relatively superficially located frontal and nasal bones were often accompanied by fractures of the skull base. Fracture etiology influenced fracture morphology such that vehicular trauma resulted in a relatively higher number of severely displaced and comminuted fractures than did other trauma etiologies. This study provides examples of fractures that, when found, should prompt veterinarians to look for additional injuries in specific locations. In addition, it further highlights the need for thorough CT evaluation of the entire CMF region, even when clinically apparent fractures appear relatively superficial.